Penerapan Metode Weighted Product (WP) Dalam Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Pada PT. Agrodehasen Bengkulu - Reno Supardi; Aji Sudarsono (UNIVED Press, 2023)
PT. Agrodehasen Bengkulu, one of the universities engaged in agriculture, to increase the resources of its employees in improving the quality of work is of course supported and influenced by the performance of employees who are competent in their fields. Where at PT. Agrodehasen Bengkulu in giving awards to the best employees every year so far it is still done manually, this certainly can increase employee morale at work and always run a business by fulfilling several criteria set by PT Agrodehasen. In this decision support system it can help calculate all the criteria in which this system uses a Weighted Product (WP) method. This method is a simple method with multiplication to link attribute ratings, where each attribute rating must be raised to the power of the attribute in question. there are four criteria, namely attendance, cooperation, quantity of work and responsibility where each employee will have these criteria. In this case, to determine the best employee is done by adding up the weight of the performance rating on each alternative for all attributes